Pathophysiological effects of particulate matter air pollution on the central nervous system - Joshua C Wright; Yuchuan Ding (Wolters Kluwer Medknow Publications, 2016)
Particulate matter (PM) air pollution is a leading public health concern across most of the populated world. Elevated PM levels cause both acute increases in cardiovascular mortality and the development of long-term neurological pathology. Upon inhalation, PM reaches the brain through entry into pulmonary capillaries and directly through the olfactory mucosa. Population-based and animal studies reveal decreases in brain size and increases in inflammatory markers following long-term exposure to elevated PM concentrations. In vitro, cell culture studies indicate that components of PM air pollution are neurotoxic. In addition to direct effects on the central nervous system (CNS), PM induces aberrant local and systemic inflammatory responses that can induce and exacerbate cerebral injury. Hypertension and decreased cerebral blood flow velocity are observed within days of increased PM exposure and may contribute to short-term rises in mortality rate. Substantial epidemiological evidence links PM concentration with both short-term and long-term risk of stroke. It has been suggested that the increased stroke risk is due to potentiation of cerebrovascular inflammation, endothelial cell dysfunction, reactive oxygen species production, and atherosclerosis. This review examines the pathophysiological mechanisms by which PM damages the CNS and the cerebrovasculature.